MicroRNAs in Vertebrate Synapse Development - Roberto Fiore; Gerhard Schratt (The Scientific World Journal)
MicroRNAs are a relatively new class of small noncoding RNAs that play an important role in post-transcriptional gene regulation during development and disease. MicroRNAs are abundant in the vertebrate nervous system where they appear to function during neuronal fate determination and early differentiation. It is now becoming increasingly clear that microRNAs are also involved in later stages of neuronal development, namely, the formation and plasticity of synapses. Furthermore, first examples are emerging that microRNAs might contribute to the etiology of neuronal diseases characterized by synaptic dysfunction. This review will summarize the recent examples that describe a function of microRNAs in synapse formation, plasticity, and disease, and discuss future directions that promise to shed light on microRNA regulation by synaptic activity and microRNA function in higher cognitive functions, such as learning and memory.